The Tariff Debate of 1909 and the New Tariff Act - Taussig, F. W. (Quarterly Journal of Economics, 1909)
The "true principle, " of equalizing cost of production, virtually new in 1908, 2. — Its fallaciousness, 2. — High wages and cost of production, 4. — Significance of the "true principle" as a concession to the demand for revision, 5. — Character of the debate of 1909, 7. — Crass protectionism, 9. — The Bill before the Ways and Means Committee, 11. — German comments pigeonholed, 13. — Action of the House, 15. — Situation in the Senate; log-rolling brings advances in duty, 16. — Conference Committee settles details, 18. — Duty on hides abolished, 19. — Duties on lumber and iron reduced, 21. — Iron and steel duties lowered, 24. — Shoes and leather, 25. — Advances on cotton goods, hosiery, silks, 27. — Economic characteristics of these industries, 31. — Insignificant changes on wool and woollens, 31, and on sugar, 33. — Sugar from the Philippines free, 34. — Advances on petty items, "jokers, " 35. — Maximum and minimum provisions, 36. — Conclusion 38.